A hydrocracking method for producing low aromatic wax oil from heavy distillate oil
By using a hydrogenation catalyst of a carrier and an active metal component to treat heavy distillate oil, the problem of insufficient catalyst activity stability in the prior art is solved, and efficient production of low aromatic wax oil is achieved, and product quality is improved.
Patent Information
- Application Number
- CN202111258153.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-27
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-10-27
AI Technical Summary
The existing hydrocracking technology is difficult to effectively treat heavy distillate oil with dry points exceeding 650°C, resulting in insufficient catalyst activity stability and product quality not meeting standards.
A hydrogenation catalyst comprising a support and an active metal component supported on the support is adopted, the support contains a non-amorphous mesoporous acidic material and a Y-type molecular sieve, and the active metal component is a Group VIII metal element and a Group VIB metal. element.
By this method, the total aromatic content in the tail oil, especially the monocyclic aromatic hydrocarbon content, can be significantly reduced, and the quality of the product can be improved, making it more suitable as FCC feed.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of chemical industry, and in particular to a method for producing low aromatic wax oil by hydrocracking from heavy distillate oil. Background Art
[0002] As crude oil becomes heavier and inferior, the conversion of heavy distillate oil has become a difficult problem in oil refining technology. Hydrocracking is one of the key technologies for lightening oil products. In the processing of heavy oil products, polycyclic hydrocarbons, especially cycloalkanes and aromatic hydrocarbons with three or more rings, accumulate in the circulating oil, resulting in reduced catalyst activity and shortened operating cycles.
[0003] Hydrocracking technology is one of the classic means of hydrogenation conversion of heavy distillate oil, with the characteristics of high product quality, long service life, flexible operation, etc. However, when used to process heavy distillates, especially heavy distillates with a dry point greater than 650°C, there are often problems such as insufficient catalyst activity stability and product quality that does not meet requirements.
[0004] Improving the processing capacity of heavy distillate oil in hydrocracking technology mainly depends on hydrocracking catalyst. Hydrocracking catalyst is a bifunctional catalyst that has both cracking activity and hydrogenation activity, that is, it contains both acidic components and hydrogenation active components. In order to meet different requirements for hydrocracking products, it is necessary to adaptively adjust the acidic components and hydrogenation active components in the catalyst.
[0005] Acidic components can be divided into two categories according to the degree of crystallization: molecular sieves and amorphous silica-alumina. Compared with molecular sieves, amorphous silica-alumina has a simple preparation method, low cost, larger pore size, larger silica-alumina ratio adjustment range and lower acid density. It is particularly suitable for processing macromolecular raw materials, such as heavy oil and residual oil; it is often used in catalysts that require lower acid density, such as hydrocracking catalysts and hydroisomerization catalysts with high middle distillate selectivity. Amorphous silica-alumina is an acidic carrier for many industrial amorphous catalysts and an important component of many molecular sieve catalysts, but the common disadvantage of amorphous silica-alumina materials is low cracking activity.
[0006] For hydrocracking catalysts, the improvement of catalyst performance requires, on the one hand, further improvement of hydrogenation performance; on the other hand, it requires suitable acidic components so that the cracking or isomerization performance can match the target product. Selecting molecular sieves or mesoporous materials, or even solid superacids, can adjust the properties of the acidic components within a larger range, thereby optimizing the acidic function of the catalyst. However, the space for adjusting the performance of the hydrogenation component is limited. Although precious metals can be used as hydrogenation components, they generally cannot process sulfur-containing raw materials. Therefore, the hydrogenation component of industrial hydrocracking catalysts generally selects non-precious metals as hydrogenation components. The hydrogenation activity of non-precious metals is lower than that of precious metals, and often cannot meet the requirements. How to improve the hydrogenation performance of the catalyst has become a problem that some hydrocracking catalysts need to solve.
[0007] It is of great significance to reduce the aromatic content of heavy fractions. The low aromatic heavy fractions can be used as feedstock for catalytic cracking to produce high-octane gasoline or olefins. Whether it is the production of gasoline or olefins, the lower the aromatic content in the feedstock, the higher the liquid yield of the catalyst. Generally, with the decrease of aromatic content, the content of paraffins and cycloalkanes will increase accordingly. The higher the content of paraffins, the more beneficial it is to improve the olefin yield; higher cycloalkanes are beneficial to improving the octane number of gasoline fractions.
[0008] For the processing of heavy distillate oil, the conventional processing methods are catalytic cracking and coking. With these two processing methods, the quality of diesel fraction is relatively poor. The typical catalytic cracking process is to produce gas, gasoline, diesel, heavy oil (which can be recycled) and coke through cracking reaction at about 500℃, 2-4 atmospheres and contact with catalytic cracking catalyst. The yield of reaction products is closely related to the properties of raw materials, reaction conditions and catalyst performance. Under general industrial conditions, the gas yield is about 10%~20%, mainly C3 and C4, and the olefin content is about 50%; the gasoline yield is about 30%~60%, the research octane number is about 80~90, and the stability is also good; the diesel yield is about 0~40%, and the cetane number is low due to the presence of more aromatics; the cetane number of diesel obtained by catalytic cracking of heavy oil is even lower, and the oxidation stability is also poor.
[0009] Similarly, vacuum residue can be processed into 70% to 80% distillate oil after coking. Coking gasoline and coking diesel have high content of unsaturated hydrocarbons, high content of non-hydrocarbon compounds such as sulfur and nitrogen, and poor stability. They must be processed through hydrofining and other processes before they can be used as engine fuel. If the quality of oil products is improved through a suitable hydrogenation process, it is not necessary to use coking technology for processing. After all, the value increase of this method is lower than that of catalytic cracking.
[0010] Unlike catalytic cracking and coking, hydrogenation, especially hydrocracking, can convert heavy fractions into fuel oil. However, conventional hydrocracking technology generally processes distillate oil components with a dry point not exceeding 550°C. For fractions with a dry point exceeding 650°C and oil products with a high metal content, residual oil hydrogenation is more often used for processing.
[0011] For some oil products, such as deasphalted oil (DAO) or residue hydrothermal conversion oil products, these oil products are characterized by high dry point, up to 680℃, or higher; high aromatic content, up to 70% or more, low metal content, Ni+V content is generally less than 1ppm, and can be used as a refining product for conventional hydrocracking units, mainly used to produce lubricating oil raw materials and catalytic cracking raw materials. How to process these oil products into high-value products, especially chemical raw materials, such as ethylene, propylene, butadiene, BTEX, etc., is a difficult point for hydrocracking. If hydrocracking is used to produce suitable catalytic cracking raw materials or chemical raw materials through reasonable grading, it will be a better choice.
[0012] Chinese patent CN101094720 proposes a hydrocracking catalyst for a mixture of vacuum gas oil (VGO) and demetallized oil (DMO), using MCM-41 as the main active component, and it is believed that VGO / DMO can be converted into hydrocarbon products with shorter carbon chains.
[0013] Chinese Patent CN 110776953 and Chinese Patent CN 110776954 propose a method for treating heavy hydrocarbon feedstocks including fixed bed hydroprocessing, the method including a series of specific steps, including a fixed bed hydroprocessing step, a deasphalting step of a heavy component produced by the fixed bed hydroprocessing step, a fixed bed hydrocracking step of a DAO component, an ebullated bed hydrocracking step of an asphalt component and a deasphalting step of a heavy component produced by the ebullated bed hydrocracking step.
[0014] Chinese patent CN 110835550 proposes a hydrocracking method for producing chemical raw materials, which comprises: introducing hydrocracking raw materials into a hydropretreatment reaction zone and a hydrocracking reaction zone in sequence for hydrogenation reaction to obtain a hydrocracking effluent; then fractionating the hydrocracking effluent; wherein the hydrocracking raw materials contain a VGO fraction and a DAO fraction, and the DAO fraction accounts for 10-30% by weight of the total amount of the hydrocracking raw materials, and the hydrogen partial pressure in the hydrocracking reaction zone is 20-80% of the hydrogen partial pressure in the hydropretreatment reaction zone. The method provided by the present invention can greatly increase the heavy naphtha yield of the hydrocracking unit, while also taking into account the production of high-quality DCC feed.
[0015] Chinese patent CN104611051B proposes a method for hydrocracking of high-drying point heavy distillate oil, where the high-drying point heavy distillate oil and hydrogen enter the first stage reaction zone for hydrofining reaction, and the first stage denitrification rate is controlled to be 60%-95%; the reaction effluent enters the separator for separation, and the resulting liquid and hydrogen enter the second stage reaction zone for hydrofining reaction; the second stage reaction effluent can be mixed with supplementary hydrogen and enter the third stage reaction zone for hydrocracking reaction; the hydrogenation reaction effluent is separated and fractionated to obtain various hydrocracking products. The invention is equipped with a commercial catalyst available on the market.
[0016] In the prior art, the blending method is generally adopted, and the blending ratio is no more than 30%. Therefore, there is an urgent need in the art for a method to fully process heavy fractions and produce low aromatic tail oil fractions. Summary of the invention
[0017] The object of the present invention is to provide a method for fully processing a heavy fraction and producing a low aromatic wax oil fraction.
[0018] In order to achieve the above-mentioned object, the present invention provides a hydrocracking method for producing low aromatic wax oil from heavy distillate oil, wherein under hydrogenation conditions, heavy distillate oil and hydrogen are contacted with a hydrogenation catalyst; the heavy distillate oil is a fraction with a dry point of not less than 650° C., a metal content of less than 20 ppm, and a high aromatic content of more than 60% by weight; the hydrogenation catalyst comprises a carrier and an active metal component loaded on the carrier; based on the total mass of the hydrogenation catalyst, the content of the carrier is 50-88% by weight; the carrier contains a non-amorphous mesoporous acidic material and a Y-type molecular sieve; the content of the Y-type molecular sieve in the carrier is 1-12% by weight; and the active metal component is a metal element of Group VIII and a metal element of Group VIB.
[0019] Optionally, based on the total mass of the hydrogenation catalyst, the content of the carrier is 58-77.5% by weight; the content of the Y-type molecular sieve in the carrier is 1.2-8% by weight, preferably 2-4.5% by weight.
[0020] Optionally, the content of Group VIB metals based on the total amount of the catalyst and calculated as oxide is 15-35% by weight, preferably 18-32% by weight, and more preferably 20-30% by weight; the content of Group VIII metals based on the total amount of the catalyst and calculated as oxide is 0.5-10% by weight, preferably 1-8% by weight, and more preferably 2-8% by weight.
[0021] Optionally, the Group VIII metal element is cobalt and / or nickel, and the Group VIB metal element is molybdenum and / or tungsten; preferably, the Group VIII metal element is nickel, and the Group VIB metal element is tungsten.
[0022] Optionally, in the porous structure, the pore diameter of the pores is in the range of 5-15 nm, preferably in the range of 6-12 nm; the specific surface area of the carrier is 190-320 m 2 / g, preferably 22-280m 2 / g; the pore volume of the carrier is 0.5-0.8mL / g, preferably 0.55-0.75mL / g; the pore concentration value of the pores is not less than 0.5, preferably not less than 0.75.
[0023] Optionally, pores with pore diameters in the range of 3-50 nm account for more than 30% of the total pore volume.
[0024] Optionally, the carrier is a non-amorphous mesoporous acidic material; preferably, the non-amorphous mesoporous acidic material is a silicon-aluminum composite oxide.
[0025] Optionally, the hydrogenation catalyst is prepared according to the following steps:
[0026] S1, impregnating the support with an aqueous solution containing a compound of a Group VIII metal and a compound of a Group VIB metal to obtain an impregnated support;
[0027] S2, subjecting the impregnated support to a first drying and a first calcination.
[0028] Optionally, the compound of the Group VIII metal is selected from at least one of nitrates, chlorides, sulfates, formates, acetates, phosphates, citrates, oxalates, carbonates, basic carbonates, hydroxides, phosphates, phosphides, sulfides, aluminates, molybdates, tungstates and water-soluble oxides of nickel and cobalt; preferably selected from at least one of nickel nitrate, nickel sulfate, nickel acetate, basic nickel carbonate, cobalt nitrate, cobalt sulfate, cobalt acetate, basic cobalt carbonate, cobalt chloride and nickel chloride; the compound containing the Group VIB metal is selected from at least one of molybdic acid, paramolybdic acid, molybdates, paramolybdates, tungstic acid, metatungstic acid, ethylmetungstic acid, tungstates, metatungstates and ethylmetungstic acid.
[0029] Optionally, the aqueous solution containing the compound of the Group VIII metal and the compound of the Group VIB metal further contains an organic additive, and the organic additive is selected from organic acids and organic amines; the molar ratio of the organic additive to the Group VIII metal element is 0.1-10, preferably 0.4-8.
[0030] Optionally, in step S1, the impregnation conditions include: the impregnation temperature is 5-150°C, and the impregnation time is 0.5-12 hours; in step S2, the first drying treatment conditions include: the drying temperature is 50-300°C, preferably 150-250°C, and further preferably 110-180°C; the drying time is 1-12 hours, preferably 2-8 hours; the first calcination conditions include: the calcination temperature is 350-550°C, preferably 400-500°C; the calcination time is 1-8 hours, preferably 2-6 hours.
[0031] Optionally, the method for preparing the carrier comprises:
[0032] SS1, mixing pseudo-thin diatomite, amorphous silicon aluminum oxide, molecular sieve and sesbania powder to obtain a first mixed powder; or mixing pseudo-thin diatomite, amorphous silicon aluminum oxide, molecular sieve, methyl cellulose and sesbania powder to obtain a second mixed powder;
[0033] SS2, mixing the first mixed powder or the second mixed powder with a nitric acid solution, kneading and extruding to obtain an extruded strip;
[0034] SS3. subjecting the extruded strip to a second drying and a second calcination.
[0035] Optionally, in step SS1, the weight ratio of the pseudo-thin alumina, the amorphous silica-aluminum oxide, the molecular sieve and the sesbania powder is 30-75:20-55:0.8-40:1-5; preferably 40-70:25-50:1-10:2-4; or the weight ratio of the pseudo-thin alumina, the amorphous silica-aluminum oxide, the molecular sieve, the methyl cellulose and the sesbania powder is 30-75:20-55:0.8-40:0-3:1-5; preferably 40-70:25-50:1-10:0-2:2-4; in step SS2, the amount of the nitric acid solution used is 0.5-3mL per 100g of the mixed powder.
[0036] Optionally, the content of SiO2 in the pseudo-thin diatomite is less than 0.1wt%, the content of Fe2O3 is less than 0.01wt%, the content of Na2O is less than 0.01wt%, the content of water is less than 3wt%, and the loss on ignition is 15-38%; the pore volume of the pseudo-thin diatomite is 0.60-1.1mL / g, and the specific surface area is 180-380m 2 / g; the characteristics of the amorphous silicon aluminum oxide include: a SiO2 content of 15-55%, an Al2O3 content of 45-85%, and a bulk density of 250-450g / L; the molecular sieve is a Y-type molecular sieve; the mass concentration of the nitric acid solution is: 0.5-4.0%.
[0037] Optionally, in step SS2, the mixing conditions include: temperature of 10-40°C, time of 1-10 minutes; in step SS3, the second drying conditions include: temperature of 100-130°C, time of 3-20 hours; the second roasting conditions include: temperature of 400-600°C, time of 2-10 hours, and air flow of 20-50L / h.
[0038] Optionally, the hydrogenation conditions include: temperature of 200-650°C, preferably 300-510°C; hydrogen partial pressure of 3-24MPa, preferably 4-10MPa; liquid hourly volume space velocity of the raw material of 0.1-50h -1 , preferably 2-40h -1 .
[0039] Through the above technical scheme, the present invention provides a hydrocracking method for producing low aromatic wax oil from heavy distillate oil. The method is used to produce low aromatic wax oil, and the total aromatic content in the product is low, and the content of monocyclic aromatics is even lower. The product is suitable as FCC feed and has higher performance.
[0040] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0041] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0042] The invention provides a hydrocracking method for producing low aromatic wax oil from heavy distillate oil. Under hydrogenation conditions, heavy distillate oil and hydrogen are contacted with a hydrogenation catalyst; the heavy distillate oil is a fraction with a dry point of not less than 650° C., a metal content of less than 20 ppm, and a high aromatic content of more than 60% by weight; the hydrogenation catalyst comprises a carrier and an active metal component loaded on the carrier; based on the total mass of the hydrogenation catalyst, the content of the carrier is 50-88% by weight; the carrier contains a non-amorphous mesoporous acidic material and a Y-type molecular sieve; the content of the Y-type molecular sieve in the carrier is 1-12% by weight; and the active metal component is a metal element of Group VIII and a metal element of Group VIB.
[0043] The heavy distillate oil mentioned in the present invention refers to the distillate oil obtained by distilling or other processing methods of petroleum fractions, and common ones include DAO (deasphalted oil), some VGO (vacuum gas oil), etc. The oxygen content in general raw oil is less than 0.5%.
[0044] The present invention does not impose too many restrictions on other properties of heavy distillate oil, but needs to consider the requirements of equipment and process during processing, such as the content of components such as Cl and F. The total metal content in the feedstock oil, mainly Ni and V, is generally required to be no higher than 20ppm.
[0045] The heavy distillate oil mentioned in the present invention is required to have a higher dry point, and the temperature of the 95% point of the distillation process of the distillate oil is analyzed by simulated distillation, and is not lower than 620° C. There is no restriction on the initial distillation point of the distillate oil and the temperature of other distillation sections.
[0046] The heavy distillate oil mentioned in the present invention has no limitation on the nitrogen content and sulfur content, but the residual carbon is required to be within 10%, preferably less than 5%, and most preferably less than 3%.
[0047] The heavy distillate oil mentioned in the present invention does not impose too many restrictions on the density and hydrogen content of the oil product, but the density is lower than 0.98 g / cm³, preferably lower than 0.96 g / cm³, and most preferably lower than 0.95 g / cm³. The hydrogen content is not lower than 10.5%, preferably higher than 10.8%, and most preferably higher than 11.0%.
[0048] The aromatic content of the heavy distillate oil mentioned in the present invention is not limited in any way, but generally, the oil products that meet the distillation range and metal content restrictions have a relatively high aromatic content, generally higher than 60%, and more often higher than 70% or even higher. For the production of low aromatic diesel, the lower the aromatic content, the more advantageous it is.
[0049] The hydroprocessing method improved by the present invention is fixed bed hydrogenation, and a moving bed or other processing method can also be used. The present invention is mainly used for a fixed bed reactor. The present invention does not limit the implementation method of the fixed bed, whether it is an axial adiabatic fixed bed reactor, a radial adiabatic fixed bed reactor, or a tubular fixed bed reactor.
[0050] The tail oil mentioned in the present invention refers to a product with a fraction range greater than 350° C. Specifically, it refers to a product tail oil that has a similar distillation range or a significantly reduced dry point after hydrogenation treatment, although the composition is different from that of the feedstock oil.
[0051] The tail oil mentioned in the present invention refers to the fraction greater than 350°C after being hydrotreated and the process still has a certain conversion rate, through oil product cutting. Compared with the feed oil, the hydrogen content of the tail oil will be greatly improved. In terms of composition, aromatics will be greatly reduced, while the content of paraffins and cycloalkanes will be significantly improved. This part of the tail oil can continue to be circulated and converted, and can also be used as feed oil for other counting devices, such as FCC feed, etc. For heavy distillate oil, adding hydrogen as much as possible is the key to further conversion. In FCC feed, the hydrogen content of the tail oil is an important control indicator, and the hydrogen content is generally required to be not less than 12%. In addition, if the aromatic content is reduced by pure hydrogenation, due to the existence of thermodynamic limitations, the degree of aromatic saturation is limited, and deep hydrogenation or removal of aromatics is required. Therefore, it is necessary to use a combination of hydrorefining and hydrocracking / hydrogenation reforming catalysts to reduce the aromatic content.
[0052] According to the present invention, based on the total mass of the hydrogenation catalyst, the content of the carrier may be 58-77.5% by weight; the content of the Y-type molecular sieve in the carrier may be 1.2-8% by weight, preferably 2-4.5% by weight.
[0053] According to the present invention, the content of Group VIB metal based on the total amount of catalyst and calculated as oxide can be 15-35% by weight, preferably 18-32% by weight, and further preferably 20-30% by weight; the content of Group VIII metal based on the total amount of catalyst and calculated as oxide can be 0.5-10% by weight, preferably 1-8% by weight, and further preferably 2-8% by weight.
[0054] According to the present invention, the metal element of Group VIII may be cobalt and / or nickel, and the metal element of Group VIB may be molybdenum and / or tungsten; preferably, the metal element of Group VIII may be nickel, and the metal element of Group VIB may be tungsten.
[0055] As a preferred embodiment of the present invention, in the porous structure, the pore diameter of the pores is in the range of 5-15 nm, preferably in the range of 6-12 nm; the specific surface area of the carrier is 190-320 m 2 / g, preferably 22-280m 2 / g; the pore volume of the carrier is 0.5-0.8mL / g, preferably 0.55-0.75mL / g; the pore concentration value of the pores is not less than 0.5, preferably not less than 0.75.
[0056] As a preferred embodiment of the present invention, the pores with pore diameters in the range of 3-50 nm account for more than 30% of the total pore volume.
[0057] According to the present invention, the carrier may be a non-amorphous mesoporous acidic material; preferably, the non-amorphous mesoporous acidic material may be a silicon-aluminum composite oxide.
[0058] In the present invention, the hydrogenation catalyst can be prepared according to the following steps:
[0059] S1, impregnating the support with an aqueous solution containing a compound of a Group VIII metal and a compound of a Group VIB metal to obtain an impregnated support;
[0060] S2, subjecting the impregnated support to a first drying and a first calcination.
[0061] In the present invention, the metal element of the group VIII and the metal element of the group VIB can be loaded on the carrier at the same time, or the metal element of the group VIII and the metal element of the group VIB can be loaded on the carrier separately. When the metal element of the group VIII and the metal element of the group VIB are loaded on the carrier separately, the loading order of the metal element of the group VIII and the metal element of the group VIB is not particularly limited, and the metal element of the group VIII can be loaded first and then the metal element of the group VIB, or the metal element of the group VIB can be loaded first and then the metal element of the group VIII, or the metal element of the group VIII and the metal element of the group VIB can be loaded at intervals. Interval loading of the metal element of the group VIII and the metal element of the group VIB is suitable for the situation that the metal element of the group VIII and the metal element of the group VIB are loaded on the carrier in multiple times. Preferably, the metal element of the group VIII and the metal element of the group VIB are loaded on the carrier at the same time, so that the simplicity of the process can be improved and the efficiency can be improved.
[0062] In the present invention, the impregnation solution can be prepared by using a compound containing a metal element of Group VIII and a compound containing a metal element of Group VIB. The specific types of the compound containing a metal element of Group VIII and the compound containing a metal element of Group VIB can be selected according to the solvent of the impregnation solution, so as to be dispersed in the solvent to form a stable impregnation solution. Preferably, the solvent of the impregnation solution is water, in which case the compound containing a metal element of Group VIII is preferably a water-soluble compound containing a metal element of Group VIII, and the compound containing a metal element of Group VIB is preferably a water-soluble compound containing a metal element of Group VIB.
[0063] As a preferred embodiment of the present invention, the compound of the Group VIII metal is selected from at least one of nitrates, chlorides, sulfates, formates, acetates, phosphates, citrates, oxalates, carbonates, basic carbonates, hydroxides, phosphates, phosphides, sulfides, aluminates, molybdates, tungstates and water-soluble oxides of nickel and cobalt; preferably selected from at least one of nickel nitrate, nickel sulfate, nickel acetate, basic nickel carbonate, cobalt nitrate, cobalt sulfate, cobalt acetate, basic cobalt carbonate, cobalt chloride and nickel chloride; the compound containing the Group VIB metal is selected from at least one of molybdic acid, paramolybdic acid, molybdate, paramolybdate, tungstic acid, metatungstic acid, ethyl metatungstic acid, tungstate, metatungstate and ethyl metatungstic acid. The content of the compound containing the Group VIII metal element and the compound containing the Group VIB metal element in the impregnation solution can be selected according to the number of impregnations, so as to make the loading amount of the Group VIII metal element and the Group VIB metal element on the carrier meet the requirements.
[0064] According to the present invention, the aqueous solution containing the compound of the metal of group VIII and the compound of the metal of group VIB may also contain an organic additive, and the organic additive may be selected from organic acids and organic amines; the organic acid refers to an organic compound containing at least one carboxyl group (-COOH) in the molecular structure, and the organic amine refers to an organic compound containing at least one amine group (-NH2) in the molecular structure. Preferably, the organic acid contains at least two carboxyl groups in the molecular structure, and the organic amine contains at least two amine groups in the molecular structure. The organic additive is preferably selected from citric acid, aminotriacetic acid, ethylenediamine and ethylenediaminetetraacetic acid. More preferably, the organic additive is selected from organic carboxylic acids, such as citric acid. The content of the organic additive can be selected according to the content of the compound containing the metal element of group VIII. The molar ratio of the organic additive to the metal element of group VIII in terms of element may be 0.1-10, preferably 0.4-8, more preferably 0.5-4, further preferably 0.8-2, and further preferably 0.9-1.5, such as 0.95-1.2.
[0065] According to the present invention, in step S1, the conditions for the impregnation may include: an impregnation temperature of 5-150°C, and an impregnation time of 0.5-12 hours; in step S2, the conditions for the first drying treatment include: a drying temperature of 50-300°C, preferably 150-250°C, and further preferably 110-180°C; a drying time of 1-12 hours, preferably 2-8 hours; the conditions for the first roasting include: a roasting temperature of 350-550°C, preferably 400-500°C; and a roasting time of 1-8 hours, preferably 2-6 hours.
[0066] According to the present invention, the method for preparing the carrier may include:
[0067] SS1, mixing pseudo-thin diatomite, amorphous silicon aluminum oxide, molecular sieve and sesbania powder to obtain a first mixed powder; or mixing pseudo-thin diatomite, amorphous silicon aluminum oxide, molecular sieve, methyl cellulose and sesbania powder to obtain a second mixed powder;
[0068] SS2, mixing the first mixed powder or the second mixed powder with a nitric acid solution, kneading and extruding to obtain an extruded strip;
[0069] SS3. subjecting the extruded strip to a second drying and a second calcination.
[0070] According to the present invention, in step SS1, the weight ratio of the pseudo-thin diatomite, the amorphous silica-aluminum oxide, the molecular sieve and the sesbania powder is 30-75:20-55:0.8-40:1-5; preferably 40-70:25-50:1-10:2-4; or the weight ratio of the pseudo-thin diatomite, the amorphous silica-aluminum oxide, the molecular sieve, the methyl cellulose and the sesbania powder is 30-75:20-55:0.8-40:0-3:1-5; preferably 40-70:25-50:1-10:0-2:2-4; in step SS2, the amount of the nitric acid solution used is 0.5-3mL per 100g of the mixed powder.
[0071] As a preferred embodiment of the present invention, the content of SiO2 in the pseudo-thin diatomite is less than 0.1wt%, the content of Fe2O3 is less than 0.01wt%, the content of Na2O is less than 0.01wt%, the content of water is less than 3wt%, and the loss on ignition is 15-38%; the pore volume of the pseudo-thin diatomite is 0.60-1.1mL / g, and the specific surface area is 180-380m 2 / g; the characteristics of the amorphous silicon aluminum oxide include: SiO2 content of 15-55%, Al2O3 content of 45-85%, bulk density of 250-450g / L; the molecular sieve is Y-type molecular sieve; the mass concentration of the nitric acid solution is: 0.5-4.0%.
[0072] According to the present invention, in step SS2, the mixing conditions may include: a temperature of 10-40°C and a time of 1-10 minutes; in step SS3, the second drying conditions may include: a temperature of 100-130°C and a time of 3-20 hours; the second roasting conditions may include: a temperature of 400-600°C, a time of 2-10 hours, and an air flow rate of 20-50L / h.
[0073] According to the present invention, the hydrogenation conditions may include: a temperature of 200-650°C, preferably 300-510°C; a hydrogen partial pressure of 3-24MPa, preferably 4-10MPa; a liquid hourly volume space velocity of the raw material of 0.1-50h -1 , preferably 2-40h -1 .
[0074] According to the hydrocracking method of the present invention, the catalyst is preferably presulfided before use. The presulfiding conditions may be conventional conditions in the art. For example, the presulfiding conditions may include: presulfiding with sulfur, hydrogen sulfide or sulfur-containing raw materials at a temperature of 140-370° C. in the presence of hydrogen. According to the hydrocracking method of the present invention, the presulfiding may be performed outside the reactor or in situ in the reactor.
[0075] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.
[0076] Example 1
[0077] Take SB powder (from catalyst Changling branch, produced by SASOL, dry basis 74.0%) 74.32g, Siral40 powder (from catalyst Changling branch, produced by SASOL, silicon oxide content 40.3%, dry basis 79.7%) 52.70g, molecular sieve USY-A (from catalyst Changling branch, unit cell constant 24.42Å, crystallinity 81.7%, Na2O 0.01%, dry basis 82.6%) 3.63g; add methyl cellulose 1.5g, sesbania powder 3g, mix well and set aside. Add water to 1.0mL concentrated nitric acid to 70mL, and stir at room temperature for 5 minutes. The nitric acid solution was mixed with the mixed powder, and the mixture was repeatedly kneaded for 3 times using a small extruder. Then, the extruded strips were extruded using a Ø1.6mm trilobal orifice plate. The extruded strips were dried at 120°C for 6 hours, and the dried strips were put into a roasting furnace and roasted at 550°C for 3.0 hours, maintaining an air flow rate of 30L / h, and then cooled to room temperature and taken out, which was recorded as carrier AC.
[0078] A mixed aqueous solution of nickel nitrate and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst being 25.0% by weight and nickel oxide being 7.0% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by the pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 440°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 35 cubic meters / (kg carrier•hour), thereby obtaining catalyst AS.
[0079] Example 2
[0080] Take SB powder (from catalyst Changling branch, produced by SASOL, dry basis 74.0%) 74.32g, Siral40 powder (from catalyst Changling branch, produced by SASOL, silicon oxide content 40.3%, dry basis 79.7%) 50.19g, molecular sieve USY-A (from catalyst Changling branch, unit cell constant 24.42Å, crystallinity 81.7%, Na2O 0.01%, dry basis 82.7%) 6.05g; 3g sesbania powder, mix well and set aside. Add water to 2.8mL concentrated nitric acid to 67mL, and stir at room temperature for 5 minutes. The nitric acid solution was mixed with the mixed powder, and the mixture was repeatedly kneaded for 3 times using a small extruder. Then, the extruded strips were extruded using a Ø1.6mm trilobal orifice plate. The extruded strips were dried at 120°C for 6 hours, and the dried strips were put into a roasting furnace and roasted at 600°C for 2.5 hours, maintaining an air flow rate of 25L / h. The strips were cooled to room temperature and taken out, which was recorded as carrier BC.
[0081] A mixed aqueous solution of nickel nitrate and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst being 25.0% by weight and nickel oxide being 7.0% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by the pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 450°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 35 cubic meters / (kg carrier•hour), thereby obtaining the catalyst BS.
[0082] Example 3
[0083] Take 60.40g of CE powder (from the catalyst Changling branch, produced by SASOL, dry basis 74.5%), 60.23g of Siral40 powder (from the catalyst Changling branch, produced by SASOL, silicon oxide content 40.3%, dry basis 79.7%), 8.26g of molecular sieve USY-B (from the catalyst Changling branch, unit cell constant 24.36Å, crystallinity 66.7%, Na2O 0.01%, dry basis 84.7%), and 3g of sesbania powder, mix well and set aside. Add water to 2.6mL of concentrated nitric acid to 80mL, and stir at room temperature for 5 minutes. The nitric acid solution was mixed with the mixed powder, and the mixture was repeatedly kneaded for 3 times using a small extruder. Then, the extruded strips were extruded using a Ø1.6mm trilobal orifice plate. The extruded strips were dried at 120°C for 6 hours, and the dried strips were put into a roasting furnace and roasted at 580°C for 3.0 hours, maintaining an air flow rate of 30L / h. The strips were cooled to room temperature and taken out, which was recorded as carrier CC.
[0084] A mixed aqueous solution of nickel nitrate and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst being 27.0% by weight and nickel oxide being 2.7% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by the pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 420°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 13.5 cubic meters / (kg carrier•hour), thereby obtaining the catalyst CS.
[0085] Example 4
[0086] Take 87.84g of SB powder (from the catalyst Changling branch, produced by SASOL, dry basis 74.0%), 41.41g of Siral40 powder (from the catalyst Changling branch, produced by SASOL, silicon oxide content 40.3%, dry basis 79.7%), 2.46g of molecular sieve USY-C (from the catalyst Changling branch, unit cell constant 24.51Å, crystallinity 84.6%, Na2O 0.01%, dry basis 81.2%), and 3g of sesbania powder, mix well and set aside. Add water to 2.2mL of concentrated nitric acid to 55mL, and stir at room temperature for 5 minutes. The nitric acid solution was mixed with the mixed powder, and the mixture was repeatedly kneaded for 3 times using a small extruder. Then, the extruded strips were extruded using a Ø1.6mm trilobal orifice plate. The extruded strips were dried at 120°C for 6 hours, and the dried strips were put into a roasting furnace and roasted at 620°C for 2.0 hours, maintaining an air flow rate of 20L / h, cooled to room temperature, and taken out, which was recorded as carrier DC.
[0087] A mixed aqueous solution of nickel nitrate and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst being 23.5% by weight and nickel oxide being 6.5% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by the pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 430°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 32.5 cubic meters / (kg carrier•hour), thereby obtaining the catalyst DS.
[0088] Comparative Example 1
[0089] Take CE powder (from catalyst Changling branch, produced by SASOL, dry basis 74.5%) 53.69g, Siral40 powder (from catalyst Changling branch, produced by SASOL, silicon oxide content 40.3%, dry basis 79.7%) 50.19g, molecular sieve USY-A (from catalyst Changling branch, unit cell constant 24.42Å, crystallinity 81.7%, Na2O 0.01%, dry basis 82.8%) 24.21g; add methyl cellulose 1g, sesbania powder 3g, mix well and set aside. Add water to 1.6mL concentrated nitric acid to 67mL, and stir at room temperature for 5 minutes. The nitric acid solution was mixed with the mixed powder, and the mixture was repeatedly kneaded for 3 times using a small extruder. Then, the extruded strips were extruded using a Ø1.6mm trilobal orifice plate. The extruded strips were dried at 120°C for 6 hours, and the dried strips were put into a roasting furnace and roasted at 580°C for 3.0 hours, maintaining an air flow rate of 30L / h, and then cooled to room temperature and taken out. This was recorded as carrier XC.
[0090] A mixed aqueous solution of nickel nitrate and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst being 27.0% by weight and nickel oxide being 2.7% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by the pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 420.25°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 13.5 cubic meters / (kg carrier•hour), thereby obtaining the catalyst XS.
[0091] Test Example 1
[0092] Catalysts were prepared by testing Examples 1-4 and Comparative Example 1, and the nickel content and tungsten content in each catalyst were tested based on the total amount of the catalyst and calculated as oxide; the carrier content based on the total mass of the hydrogenation catalyst; and the Y-type molecular sieve content based on the total mass of the carrier. The specific testing method was XRF, and the test results are shown in Table 1.
[0093] Table 1
[0094]
[0095] Test Example 2
[0096] This test example uses the catalysts prepared in Examples 1-4 and Comparative Example 1 to hydrocracking heavy reformed oil of residual oil, with a density of 0.9731 g / mL at 20°C; sulfur content 25530 μg / g; nitrogen content 2800 μg / g; Ni+V content <2 μg / g. Hydrogen content 10.8%; residual carbon 3.2%; asphaltenes <0.1%, total aromatics 70.3%. Distillation range ASTM-D1160, 10%, 371°C; 30%, 428°C; 50%, 494°C; 70%, 570°C; 90%, 630°C. Hydrogenation conditions: hydrogen partial pressure 13.0 MPa, volume space velocity 0.23 h -1 , hydrogen-to-oil ratio 800. The dosage of the refining agent and the modifier was 1:1, the refining agent temperature was 380°C, and the appropriate conversion rate was controlled by adjusting the modifier temperature. The reaction results of each catalyst are shown in Table 2.
[0097] Table 2
[0098] Catalyst name Catalyst activity / ℃ Total aromatics content in heavy oil Content of monocyclic aromatic hydrocarbons in heavy oil / % AS 341 22.33 15.3 BS 342 14.81 9.47 CS 342 19.9 11.4 DS 342 17.3 10.3 XS 328 26.61 17.39
[0099] It can be seen from Table 2 that, compared with the comparative agent, the catalyst provided by the present invention has a lower total aromatic content in the tail oil and an even lower content of monocyclic aromatic hydrocarbons, is suitable as an FCC feed, has higher performance, and also demonstrates the advantages of the present invention.
[0100] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0101] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0102] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A hydrocracking method for producing low aromatic wax oil from heavy distillate oil, characterized in that: Under hydrogenation conditions, a heavy distillate oil and hydrogen are contacted with a hydrogenation catalyst; the heavy distillate oil is a fraction having a dry point of not less than 650° C., a metal content of less than 20 ppm, and an aromatic content of more than 60% by weight; The hydrogenation catalyst comprises a carrier and an active metal component supported on the carrier; Based on the total mass of the hydrogenation catalyst, the content of the carrier is 50-88% by weight; The carrier contains a non-amorphous mesoporous acidic material and a Y-type molecular sieve; the content of the Y-type molecular sieve in the carrier is 1-12% by weight; The active metal components are metal elements of Group VIII and Group VIB; The non-amorphous mesoporous acidic material is a silicon-aluminum composite oxide; The preparation method of the carrier comprises: SS1, mixing pseudo-thin diatomite, amorphous silicon aluminum oxide, molecular sieve and sesbania powder to obtain a first mixed powder; or mixing pseudo-thin diatomite, amorphous silicon aluminum oxide, molecular sieve, methyl cellulose and sesbania powder to obtain a second mixed powder; SS2, mixing the first mixed powder or the second mixed powder with a nitric acid solution, kneading and extruding to obtain an extruded strip; SS3. subjecting the extruded strip to a second drying and a second calcination.
2. The hydrocracking method according to claim 1, wherein: Based on the total mass of the hydrogenation catalyst, the content of the carrier is 62-77.5% by weight; The content of the Y-type molecular sieve in the carrier is 1.2-8% by weight.
3. The hydrocracking method according to claim 2, wherein: The content of the Y-type molecular sieve in the carrier is 2-4.5% by weight.
4. The hydrocracking method according to claim 1, wherein: The content of Group VIB metal is 15-35% by weight based on the total amount of catalyst and calculated as oxide; The content of Group VIII metal calculated as oxide, based on the total amount of the catalyst, is 0.5 to 10% by weight.
5. The hydrocracking method according to claim 4, wherein: The content of Group VIB metal is 18-32% by weight based on the total amount of catalyst and calculated as oxide; The content of Group VIII metal calculated as oxide, based on the total amount of the catalyst, is 1 to 8% by weight.
6. The hydrocracking method according to claim 5, wherein: The content of Group VIB metal is 20-30% by weight based on the total amount of catalyst and calculated as oxide; The content of Group VIII metal calculated as oxide, based on the total amount of the catalyst, is 2 to 8% by weight.
7. The hydrocracking method according to claim 1, wherein: The Group VIII metal element is cobalt and / or nickel, and the Group VIB metal element is molybdenum and / or tungsten.
8. The hydrocracking method according to claim 7, wherein: The Group VIII metal element is nickel, and the Group VIB metal element is tungsten.
9. The hydrocracking method according to claim 1, wherein: The carrier has a porous structure; In the porous structure, the pores have a pore size in the range of 5-15 nm; The specific surface area of the carrier is 190-320m 2 / g; The pore volume of the carrier is 0.5-0.8 mL / g; The pore concentration value of the pores is not less than 0.
5.
10. The hydrocracking method according to claim 9, wherein: In the porous structure, the pores have a pore size in the range of 6-12 nm; The pore volume of the carrier is 0.55-0.75 mL / g; The pore concentration value of the pores is not less than 0.
75.
11. The hydrocracking method according to claim 1, wherein: The hydrogenation catalyst is prepared according to the following steps: S1, impregnating the support with an aqueous solution containing a compound of a Group VIII metal and a compound of a Group VIB metal to obtain an impregnated support; S2, subjecting the impregnated support to a first drying and a first calcination.
12. The hydrocracking method according to claim 11, wherein: The compound of the Group VIII metal is selected from at least one of nitrates, chlorides, sulfates, formates, acetates, phosphates, citrates, oxalates, carbonates, basic carbonates, hydroxides, phosphides, sulfides, aluminates, molybdates and tungstates of nickel and cobalt; The compound of the VIB group metal is selected from at least one of molybdic acid, molybdate, tungstic acid, ethyl metatungstic acid and tungstate.
13. The hydrocracking method according to claim 11, wherein: The compound of the VIB group metal is selected from one or more of metatungstate and metatungstate.
14. The hydrocracking method according to claim 12, wherein: The compound of the Group VIII metal is selected from at least one of nickel nitrate, nickel sulfate, nickel acetate, basic nickel carbonate, cobalt nitrate, cobalt sulfate, cobalt acetate, basic cobalt carbonate, cobalt chloride and nickel chloride.
15. The hydrocracking method according to claim 11, wherein: The aqueous solution containing the compound of the Group VIII metal and the compound of the Group VIB metal further contains an organic additive, and the organic additive is selected from organic acids and organic amines; The molar ratio of the organic additive to the metal element of Group VIII is 0.1-10.
16. The hydrocracking method according to claim 15, wherein: The molar ratio of the organic additive to the metal element of Group VIII calculated as the element is 0.4-8.
17. The hydrocracking method according to claim 11, wherein: In step S1, the impregnation conditions include: an impregnation temperature of 5-150°C and an impregnation time of 0.5-12 hours; In step S2, the conditions of the first drying treatment include: a drying temperature of 50-300°C; a drying time of 1-12 hours; the conditions of the first calcination include: a calcination temperature of 350-550°C; a calcination time of 1-8 hours.
18. The hydrocracking method according to claim 17, wherein: In step S2, the conditions of the first drying treatment include: a drying temperature of 150-250°C; a drying time of 2-8 hours; the conditions of the first calcination include: a calcination temperature of 400-500°C; a calcination time of 2-6 hours.
19. The hydrocracking method according to claim 17, wherein: In step S2, the conditions of the first drying treatment include: a drying temperature of 110-180°C.
20. The hydrocracking method according to claim 1, wherein: In step SS1, the weight ratio of the pseudo-alumina, the amorphous silica-alumina, the molecular sieve and the sesbania powder is 30-75:20-55:0.8-40:1-5; or The weight ratio of the pseudo-thin aluminum water stone, the amorphous silicon aluminum oxide, the molecular sieve, the methyl cellulose and the sesbania powder is 30-75:20-55:0.8-40:0-3:1-5, wherein the content of methyl cellulose is not 0; In step SS2, the amount of the nitric acid solution is 0.5-3 mL per 100 g of the first mixed powder or the second mixed powder.
21. The hydrocracking method according to claim 20, wherein: In step SS1, the weight ratio of the pseudo-alumina, the amorphous silica-alumina, the molecular sieve and the sesbania powder is 40-70:25-50:1-10:2-4; or The weight ratio of the pseudo-alumina, the amorphous silica-alumina, the molecular sieve, the methyl cellulose and the sesbania powder is 40-70:25-50:1-10:0-2:2-4.
22. The hydrocracking method according to claim 1, wherein: The content of SiO2 in the pseudo-thin diatomite is less than 0.1wt%, the content of Fe2O3 is less than 0.01wt%, the content of Na2O is less than 0.01wt%, the content of water is less than 3wt%, and the loss on ignition is 15-38%; the pore volume of the pseudo-thin diatomite is 0.60-1.1mL / g, and the specific surface area is 180-380m 2 / g; The characteristics of the amorphous silicon aluminum oxide include: SiO2 content of 15-55%, Al2O3 content of 45-85%, and bulk density of 250-450g / L; The molecular sieve is a Y-type molecular sieve; The mass concentration of the nitric acid solution is 0.5-4.0%.
23. The hydrocracking method according to claim 1, wherein: In step SS2, the mixing conditions include: temperature of 10-40° C., time of 1-10 minutes; In step SS3, the second drying conditions include: temperature of 100-130°C, time of 3-20 hours; the second calcination conditions include: temperature of 400-600°C, time of 2-10 hours, and air flow of 20-50L / h.
24. The hydrocracking method according to claim 1, wherein: The hydrogenation conditions include: temperature of 200-650°C; hydrogen partial pressure of 3-24 MPa; liquid hourly volume space velocity of the heavy distillate oil of 0.1-50 h -1 .
25. The hydrocracking method according to claim 24, wherein: The hydrogenation conditions include: temperature of 300-510°C; hydrogen partial pressure of 4-10 MPa; liquid hourly volume space velocity of the heavy distillate oil of 2-40 h -1 .
Citation Information
Patent Citations
A kind of high dry point heavy distillate oil hydrocracking method
CN104611051B
Porous carrier for hydrogenation catalyst, preparation method, hydrocracking catalyst and hydrocracking method
CN107715907A